Proposta de um Instrumento para Aferir a Esperança e sua Relação com Intenções Comportamentais dos Consumidores - Valter Afonso Vieira (RAC: Revista de Administração Contemporânea, 2011)
This paper has a main goal (a) to propose a scale for measuring hope and (b) to test the scale in a nomological literature context. A survey research was made looking for analyzing the scale proposed. A non-probabilistic and convenience sample was used, corresponding to a total of 226 business student who fulfilled the questionnaires. The adjustments of the structural equation modeling was not good, however a four factor structure was found, which is in agreement with the theory, rejecting the unidimensional feature. Thus, desire, hope, possibility and importance are the dimensions of the latent variable. The second conclusion is that, testing rival models, the best one was structure B, which has four dimensions.